2021
DOI: 10.12669/pjms.37.4.3602
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue assessment by FACIT-F scale in Pakistani cohort with Rheumatoid Arthritis (FAF-RA) study

Abstract: Objective: To fine out fatigue frequency and severity by FACIT-F scale in Pakistani cohort with rheumatoid arthritis. Methods: This study was conducted at department of Medicine division of rheumatology CPMC Lahore. After the approval of IRB, 192 patients of RA were recruited. Written, informed consent was taken, demographic details were noted, patients filled the URDU version of FACIT-F (fatigue severity scale). 5-ml of blood was taken for fasting blood sugar, viral markers and ESR by a trained phleboto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
4
16
1
Order By: Relevance
“…Next, we assessed the effect of the treatment on the degree of fatigue experienced by the patients using the FACIT-F questionnaire and the intensity of pain via the VAS scale. It should be remembered that the FACIT-Fi questionnaires and the VAS scale are used successfully outside of oncology, too [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed the effect of the treatment on the degree of fatigue experienced by the patients using the FACIT-F questionnaire and the intensity of pain via the VAS scale. It should be remembered that the FACIT-Fi questionnaires and the VAS scale are used successfully outside of oncology, too [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the occurrence of rheumatoid arthritis, the large and small joints of patients can be subject to inflammatory infiltration, resulting in joint swelling, tenderness, movement disorder, etc., which seriously affects the daily life of patients. 10 The disease modifying anti-rheumatic drug selected in this study was methotrexate, which belongs to a category of cell-cycle specific drugs. It can inhibit the proliferation and division of lymphocytes by reducing the activities of dihydrofolate reductase and formyl transferase, thus playing antiinflammatory and anti-rheumatic role.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that rituximab (RTX) may induce hypogammaglobulinemia (1). Under normal conditions, IgM provides a rapid immune response and is involved in tissue homeostasis, whereas IgG and IgA are long-lasting high-affinity antibodies, the latter mainly providing mucosal immunity (2). Objectives: The evaluate serum Ig levels (IgG, IgM, IgA) in a cohort of RA patients and potential therapeutic influences.…”
Section: Carol Davila University Of Medicine and Pharmacy Rheumatolog...mentioning
confidence: 99%
“…Background: Rheumatoid arthritis (RA) is an inflammatory, systemic autoimmune disease affecting the synovial membrane of small joints. 1 Wagan A. et al demonstrated that the frequency of fatigue in rheumatoid arthritis is 62%, 2 Hammam et al described a higher rate of fatigue associated with higher disease activity. Fatigue is as a feeling of exhaustion, also as a reduction in physical and mental capacity, 3,4 it can be measured with the scale FACIT-F (Functional Assessment of Chronic Illness Therapy-Fatigue), which evaluates the last 7 days, with a score of 0-52.…”
Section: Does the Parity Improve The Rheumatoid Arthritis Activity?mentioning
confidence: 99%
See 1 more Smart Citation